Oxidative dehydrogenation of ethylbenzene over vanadia-alumina catalysts in the presence of nitrous oxide: structure-activity relationship - Shiju, N. R.; Anilkumar, Mettu; Mirajkar, Subhash P.; Gopinath, Chinnakonda S.; Rao, B. S.; Satyanarayana, C. V. (Journal of Catalysis, 2005)
A series of vanadia-alumina catalysts with different vanadia contents were prepared by a wet impregnation method. The influence of the local structure of vanadia in these catalysts on the oxidative dehydrogenation of ethylbenzene with nitrous oxide was investigated. The use of N2O as a co-feed remarkably enhanced the styrene yield compared with the use of N-2. Characterization of these vanadia catalysts by XRD, FTIR, UV-vis, TPR, XPS, and V-51 NMR techniques suggests that the nature of the VOx species depends on the vanadia loading: the predominant species are monomeric vanadia at lower loadings, two-dimensional polyvanadates at intermediate loadings, and bulk-like V2O5 and AlVO4 at higher loadings. The rate of oxidative dehydrogenation (ODH) of ethylbenzene per vanadium atom increases with vanadia loading and reaches a maximum at 10 wt%, the loading at which the surface predominantly contains polyvanadate species. The observed variation in the selectivity of products with vanadium loading indicates that the monomeric V5+ species favors dehydrogenation, whereas bulk-like V2O5 preferentially participates in the dealkylation of ethylbenzene. The vanadium species remains at a higher oxidation state in the presence of N2O, leading to a higher styrene yield. than in a N-2 atmosphere. The ODH turnover rates increased with decreasing energy of the absorption edge in the UV-vis spectrum, at low VOx coverages of less than one monolayer on the Al2O3 surface. (c) 2005 Elsevier Inc. All rights reserved.
Keywords: absorption edge energy; Alumina; ethylbenzene; Nitrous oxide; oxidative dehydrogenation; polyvanadates; styrene; vanadia

Oxidative disproportionation of MoS2/GO to MoS2/MoO3-x/RGO : integrated and plasmonic 2D-multifunctional nanocomposites for solar hydrogen generation from near-infrared and visible regions - Patra, Kshirodra Kumar; Ghosalya, Manoj Kumar; Bajpai, Himanshu; Raj, Sreeya; Gopinath, Chinnakonda S. (Journal of Physical Chemistry C, 2019)
Two dimensional (2D) semiconductor materials have been recently demonstrated to be effective plasmonic materials and alternatives to costly noble metals. However, tuning the plasmon resonance of 2D semiconductors and integrating with another material or semiconductor for various applications, such as solar light harvesting, remains a challenge. Herein, we designed a simple and attractive method, which facilitates the diffusion of oxygen from the graphene oxide (GO) layers of the MoS2/GO (MG) composite to oxidize the MoS2 layers significantly due to thermal treatment under inert atmosphere. This is the key step in the formation of MoS2/MoO3-x/RGO (MMR) (x = 0, 0.5, and 1, and all stoichiometries co-exist), due to disproportionation of MoS2/GO, with bulk heterojunctions among the components. The observed behavior is attributed to the oxidation of Mo4+ cations (of MoS2) to higher oxidation states in MMR (Mo(5+ )and Mo6+ of MoO3-x), which also alters the valence-band electronic structure and work function of the resulting composite. The 2D MoO3-x layers with a large amount of Mo5+ oxidation states enables facile charge carrier generation due to plasmonic effect, whereas MoS2 provides active sites for catalysis. The solar H-2 generation was demonstrated in the visible and near-infrared region by combining both the plasmonic and catalytic effects in one composite. These results demonstrate the important role of RGO to provide energy-level alignment, charge carrier diffusion, and help to generate plasmonic effect in the composite.

One-dimensional multichannel g-C3N4.7 nanostructure realizing an efficient photocatalytic hydrogen evolution reaction and its theoretical investigations - Antil, Bindu; Kumar, Lakshya; Ranjan, Ravi; Shenoy, Sulakshana; Tarafder, Kartick; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Applied Energy Materials, 2021)
The emerging metal-free carbon nitride (C3N4) offers prominent possibilities for realizing the highly effective hydrogen evolution reaction (HER). However, its poor surface conductivity and insufficient catalytic sites hinder the HER performance. Herein, a one-dimensional vermicular rope-like graphitic carbon nitride nanostructure is demonstrated that consists of multichannel tubular pores and high nitrogen content, which is fabricated through a cost-effective approach having the final stoichiometry g-C3N4.7 for HER application. The present g-C3N4.7 is unique owing to the presence of abundant channels for the diffusion process, modulated surface chemistry with rich- electroactive sites from N-electron lone pairs, greatly reduced recombination rate of photoexcited exciton pairs, and a high donor concentration (4.26 x 10(17) cm(3)). The catalyst offers a visible-light-driven photocatalytic H-2 evolution rate as high as 4910 mu mol h(-1)g(-1) with an apparent quantum yield of 14.07% at band gap absorption (2.59 eV, 479 nm) under 7.68 mW cm(-2) illumination. The number of hydrogen gas molecules produced is 1.307 x 10(15) s(-1) cm(-2), which remained constant for a minimum of 18 h of repeated cycling in the HER without any degradation of the catalyst. In density functional theory calculations, a significant change in the band offset is observed due to N doping into the system in favor of electron catalysis. The theoretical band gap of a monolayer of g-C3N4.7 was enormously reduced because of the presence of additional densities of states from the doped N atom inside the band gap. These impurity or donor bands are formed inside the band gap region, which ultimately enhance the hydrogen ion reduction reaction enormously.
Keywords: carbon nitride; Density functional theory; hydrogen evolution reaction; nitrogen-rich; Photocatalyst

Oxidative and selective C-C cleavage of glycerol to glycolaldehyde with atom-like Cu on Cu-TiO2: photocatalytic water reduction with concurrent glycerol oxidation in sunlight - Bajpai, Himanshu; Nivedhitha, Thazhath R.; Dais, Elsa; Kanungo, Subhashree S.; Gopinath, Chinnakonda S. (Journal of Catalysis, 2024)
Concurrent consumption of electrons and holes for the conversion of a biomass component to value added products represents a highly efficient and sustainable approach towards utilizing renewable energy, but difficult to achieve. The integration of hydrogen production with glycerol oxidation presents a novel and sustainable approach towards achieving a circular economy. In the current study, integration of atom-like Cu-clusters onto TiO2 substrate has been achieved using a facile photo-deposition technique (TC-PDO). Also, novel synthetic approaches have been employed to augment the surface coverage of Cu on TiO2 with atom-like clusters of Cu, either by borohydride treatment on TiO2 followed by Cu-deposition (TC-200) or oxygen-vacancy creation by UV illumination followed by Cu-deposition (TC-PDO). Increased dispersion and enhanced electronic integration of Cu with TiO2 lead to a corresponding increase in the efficiency of photocatalytic hydrogen evolution (13.8 mmol/h.g for TC-PDO at pH 9). Several atom-like Cu integrated with each TiO2 particle acts as photocatalytic reactor, and the same enhances electron-hole separation as well as activity. Sustainable aspect was also studied for TC-PDO up to 25 h at pH 9. Concurrently, glycerol oxidation displays the highest selectivity to C2 product (glycolaldehyde with 70 %) with a C-C cleavage. The investigation of this process holds significant potential for the extensive and simultaneous exploitation of electrons and holes in order to achieve water splitting and glycerol oxidation towards selective value-added products formation.
Keywords: C -C Cleavage; Glycerol; nanotechnology; Photo -deposition; solar energy conversion